PACU JALUR DAN KEKELUARGAAN MASYARAKAT DESA PULAU KALIMANTING - Suroyo, Suroyo; Bonita Padang; Fito Dwi Rezky Ramadhan; Januardi, Januardi; Monica Ramadhani C; Patricia Endah S. Riski Saputra; Rosi Octariantoni; Sri Supitri Romdania; Winda Febiola; Yossy Shinta Dewi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The Pacu Jalur tradition, which is held once a year, was originally intended as an event to commemorate major Muslim holidays, such as Eid al-Fitr, Eid al-Adha, Maulid Nabi, or the commemoration of the Hijri New Year. During the Dutch colonial period, the Pacu Jalur event was used as an activity to commemorate the birthday of Queen Wihelmina (Queen of the Netherlands). Usually held in November every year. However, after the independence of Indonesia, the Pacu Jalur festival was intended to celebrate the Independence Day of the Republic of Indonesia. Pacu Jalur are usually followed by local people, neighboring districts, and even participants from neighboring countries such as Malaysia, Singapore, and Thailand. The sense of kinship that exists in the people of Pulau Kalimanting Village comes from several activities carried out together, namely maelo jalur, racing practice, and pudding night.